Архетип психосоциальной эволюции с точки зрения политического менеджмента - Донченко, Е. (Социология: теория, методы, маркетинг, 2000)
Basing on the holistic paradigm, the author has developed a model of social evolution in C.G.Jung's terms of quarter archetype. There have been analyzed the main archetype characteristics of socium according to the consequent stages of social evolution:totalitarian, authoritarian, liberal, and democratic. Informational orientation mechanisms have been studied as the factors of society consolidation.